Attitudes of college students toward Filipino in Colegio de San Juan de Letran - Espiritu, Raquel D. (Manila : National University, 2006)
This study centered on the college students of Colegio de San Juan de Letran, Intramuros Manila in the first semester of Academic year 2006-2007. It covered the factors affecting the attitude of college students towards the subject Filipino, study of Filipino subjects, their Filipino professors/instructors and their teaching strategies and techniques.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method: Descriptive Design.
Includes bibliographical references.